Diversity and Utilization of Halophytes of Hot Arid Rangelands: A Review - Singh, J P; Rathore, V S; Mangalassery, S; Dayal, Devi (Annals of Arid Zone, 2020)
Increasing agricultural production to match the predicted population growth along with reducing availability of good quality land and water is an important challenge of 21st century. This challenge is particularly more relevant in arid regions characterized by water scarcity, poor soil and high biotic pressure. Livestock production is a major livelihood activity of hot arid region and rangelands are the backbone of the traditional pasture-based livestock rearing activity. Halophytes are a vital component of vegetation in hot arid rangeland. This review focuses on the diversity, economic and ecological significances of halophytes in Indian hot arid region and provides a comprehensive summary of utilization of halophytes for forage, feed, food, source of bioactive chemicals, oilseed, energy and bio fence purposes. The potential applications of halophytes for restoration of degraded lands have also been discussed. We argue that halophytes may be suitable alternative to augment availability of agricultural products along with many ecological services particularly in saline lands. Key words: Halophyte, feed, hot arid India, ecological restoration, rangelands